Production of detergent from coconut oil - Torres, Rowena J. (College of Engineering, 1978)
The selected plant is a 5,000 sq m (0.5 ha) area in Atimonan, Quezon. There is easy access to raw materials, particularly refined coconut oil from nearby Coconut Chemicals, Philippines, Inc. The nearby ports provide for convenient delivery of the other raw materials, both from local and foreign sources (i.e. sodium and sodium silicate) and also serve as intermediate distribution centers of the detergent product. In addition, there is proximity to railway and highway transportation facilities. Water supply and utilities are adequate and waste disposal can be accomplished by water disposal. Labor is abundant and there are no restricting laws. The design capacity is 100,00 lb/day (12,500 short tons/year) of 38% active sodium alcohol sulfate detergent. This capacity is approximately 26% of the estimated total Philippine production in 1976. Operation is continuous, five days a week for an operating factor of 250 days a year.